2015
DOI: 10.25159/2520-5293/38
|View full text |Cite
|
Sign up to set email alerts
|

BEING LESBIAN, GAY, BISEXUAL, TRANSGENDER AND INTERSEX (LGBTI) STUDENTS AT A SOUTH AFRICAN RURAL-BASED UNIVERSITY: Implications for HIV prevention

Abstract: Negative attitudes towards Lesbian, Gay, Bisexual, Transgender and Intersex (LGBTI) communities exist in South Africa, regardless of the constitutional provision and anti-discriminatory policies. Cases of violence against LGBTI persons due to their sexual orientation have been reported in the media and scientific journals. This study focused on LGBTI students of a rural-based university. It explored and described their experiences in interacting with members and structures of the university community.  A quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Most of South African literature on youth and sexuality focuses on risk for ill health with less discussion of healthy relationships and pleasure. The dominant debates on LGBTI youth in South African universities focuses on knowledge, attitudes and practices, stigma and discrimination and HIV risk (Abaver et al 2014, Mavhandu-Mudzusi andNetshandama 2013;Mavhandu-Mudzusi 2014;Mavhandu-Mudzusi and Sandy 2015;Arndt and de Bruin 2006;HEAIDS and NACOSA 2014). When discussing homosexual relationships, the focus is on the impact of being 'different' and on homosexual youths' self-worth, distress, stigma, discrimination, HIV and so on (Lane et al 2008;Nduna and Jewkes 2013;Newcomb, Clerkin, and Mustanski 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most of South African literature on youth and sexuality focuses on risk for ill health with less discussion of healthy relationships and pleasure. The dominant debates on LGBTI youth in South African universities focuses on knowledge, attitudes and practices, stigma and discrimination and HIV risk (Abaver et al 2014, Mavhandu-Mudzusi andNetshandama 2013;Mavhandu-Mudzusi 2014;Mavhandu-Mudzusi and Sandy 2015;Arndt and de Bruin 2006;HEAIDS and NACOSA 2014). When discussing homosexual relationships, the focus is on the impact of being 'different' and on homosexual youths' self-worth, distress, stigma, discrimination, HIV and so on (Lane et al 2008;Nduna and Jewkes 2013;Newcomb, Clerkin, and Mustanski 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, LGBTI people in Zimbabwe often hide their sexual orientations and deny the same when questioned (Mabvurira et al 2012). This is also the case for other countries in Southern Africa, like South Africa, where LGBTI individuals may sometimes hide their sexual orientations because of fear of prejudice and discrimination (Mavhandu-Mudzusi 2014). Such reactions to prejudicial and discriminatory acts may lead to long term stress, which in turn may contribute to the development of mental health problems in this population (Meyer, Dletrich and Swartz 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Outcomes of range of research studies revealed positive and direct relationships between internalised homophobia, self-harm, suicidal ideations, and anxiety symptoms (Mavhandu-Mudzusi 2014;Mavhandu-Mudzusi and Sandy 2015). Thus, LGBTI individuals are considered a high-risk group for mental health problems.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations